User Interface/User Experience Evaluation of batiksiputri.com with The Principle of Usability Jacob Nielsen - Prihati Prihati; Oei Natalia Kristanti (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
This research aims to evaluate user interface/user experience issues and measure the usability level of batiksiputri.com. Batik Warna Alam siPutri is a micro, small, and medium enterprise (MSME) that has a website-based e-commerce, namely batiksiputri.com. This research was made using a qualitative descriptive method based on Jacob Nielsen's usability theory in determining what criteria have been applied and which have not been applied from the usability level at batiksiputri.com. The usability criteria used are Jacob Nielsen's usability criteria, namely learnability, efficiency, memorability, errors and satisfaction. The application of Jacob Nielsen usability in the evaluation of user interface design/user experience on batiksiputri.com resulted in the conclusion that the usability criteria applied in batiksiputri.com have implemented the criteria of learnability, efficiency and satisfaction well but have a few shortcomings in the criteria of memorability and error. This batiksiputri.com, requires further development in order to meet all user needs.